2005
DOI: 10.6026/97320630001028
|View full text |Cite
|
Sign up to set email alerts
|

Protein subunit interfaces: heterodimers versus homodimers

Abstract: Abstract:Protein dimers are either homodimers (complexation of identical monomers) or heterodimers (complexation of non-identical monomers). These dimers are common in catalysis and regulation. However, the molecular principles of protein dimer interactions are difficult to understand mainly due to the geometrical and chemical characteristics of proteins. Nonetheless, the principles of protein dimer interactions are often studied using a dataset of 3D structural complexes determined by X-ray crystallography. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 18 publications
2
53
2
Order By: Relevance
“…2) in 2S (r 2 = 0.41) and 3SMI (r 2 = 0.52). The data presented here for 2S and 3SMI is different from the relation shown by Zhanhua et al [12]. However, this is not true for 3SDI Fig.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…2) in 2S (r 2 = 0.41) and 3SMI (r 2 = 0.52). The data presented here for 2S and 3SMI is different from the relation shown by Zhanhua et al [12]. However, this is not true for 3SDI Fig.…”
Section: Discussioncontrasting
confidence: 69%
“…A study by Zhanhua et al showed the weak relationship of monomer length with interface area (r 2 = 0.20) and interface residues (r 2 = 0.23) in a large dataset of 170 homodimers [12]. Therefore, it is of interest to study similar relationships within the 2S, 3SMI and 3SDI subsets.…”
Section: Discussionmentioning
confidence: 96%
“…The mutant TNSALP enzymes produced have variable and possibly preferential catalytic activity of substrates, inorganic pyrophosphate, and PLP (Di Mauro et al 2002). The mutant enzymes are also often found as heterodimers which have variable catalytic activity depending on the combination of monomers composing that particular heterodimeric enzyme (Di Mauro et al 2002;Zhanhua et al 2005). These characteristics of TNSALP produced in those with mutations of the TNSALP gene help explain some of the phenotypic variability of disease in HPP.…”
Section: Discussionmentioning
confidence: 99%
“…While we could not determine if oligomer formation was due to misfolding or nonspecific association, we may have been at high risk of nonspecific association when using cysteines, which are hydrophobic, to coordinate zinc at a hydrophobic interface. Previous studies have shown that homodimeric interfaces tend to be more hydrophobic than heterodimeric interfaces 46 , though perhaps more polar character would help us avoid high-order nonspecific oligomerization in future designs.…”
Section: Discussionmentioning
confidence: 99%